2019
DOI: 10.1111/jerd.12456
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of crown fragment reattachment techniques for fractured anterior teeth: A retrospective case‐control study

Abstract: Objective Among the techniques used by pediatric dentists for the crown fracture is the fragment reattachment. The aim of this study was to evaluate the long‐term survival of the tooth reattachment in comparison to the composite restoration technique. Methods The study included 67 patients aged 7‐9 years (males 38/56.7%; females 29/43.3%), with noncomplicated fractures of permanent teeth. The patients were divided into two groups; group A included 32 patients (males 18/56.2%; females 14/43.8%; total number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Similar results were obtained in a retrospective case-control study conducted by Sarapultseva and Sarapultsev, 19 Mendes et al, 20 and Karre et al 21 who showed a success rate of the patients treated with a biological approach and it could be indicated a good alternative to all other techniques. 22 …”
Section: Discussionsupporting
confidence: 81%
“…Similar results were obtained in a retrospective case-control study conducted by Sarapultseva and Sarapultsev, 19 Mendes et al, 20 and Karre et al 21 who showed a success rate of the patients treated with a biological approach and it could be indicated a good alternative to all other techniques. 22 …”
Section: Discussionsupporting
confidence: 81%
“…These results were in accordance with earlier published data by Brambilla and Cavallè, 33 who proposed that in case of This study is similar to previously published reports which showed that a distinct proportion of reattached fragments will be lost. 9,14,16,17 Such events mostly occurred within the first year after the accident in the present sample (Table 2). Interestingly, most of the fragments were re-reattached again with an adequate high survival rate (Figure 2).…”
Section: Discussionmentioning
confidence: 66%
“…The latter technique is a good first choice in dental practice due to the possibility of restoring the individual crown form (shape, color, translucence, and surface texture), aesthetics, and functionality in the shortest amount of time (Figure 1). Furthermore, this treatment approach is arguably minimally invasive, simple to perform and, therefore, an efficient restoration technique 9‐12 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations